Adaptive integration algorithm for stiff ordinary differential equations - Čiegis, Raimondas; Suboč, Olga (Lietuvos matematikos rinkinys, 1999)
The accuracy of one adaptive integration algorithm is investigated. The accuracy of the discretization is estimated by comparing the discrete and exact stability factors. It is proved that the classical stiffness definition is sufficient for explicit schemes. The complexity of implicit schemes depends on the distribution of eigenvalues of the systems matrix and the information about minimal and maximal values of eigenvalues is not sufficient. Results of numerical experiments are presented.